The Association Between Stress and Injury: A Prospective Cohort Study Among 186 First-Year Contemporary Dance Students - van Winden, Diana; van Rijn, Rogier M.; Savelsbergh, Geert J. P.; Oudejans, Raôul R. D.; Stubbe, Janine H. (Frontiers in Psychology, 2021)
The demanding environment that contemporary dance students are exposed to could result in high stress levels, which can influence injury susceptibility. Therefore, this study aims to investigate the association between stress and injuries. In the period between September 2016 and March 2020, four cohorts of first-year dance students (N=186; mean age 19.21±1.35 years) were followed for one academic year. Each month, general stress was assessed on a 0-100 visual analogous scale. The Oslo Sports Trauma Research Center Questionnaire on Health Problems was used on a monthly basis to monitor injuries. Injuries were defined as ‘all injuries’ (i.e., any physical complaint irrespective of need for medical attention or time-loss from dance) and ‘substantial injuries’ (i.e., leading to moderate/severe/complete reductions in training volume or performance). Mann-Whitney tests were performed to measure differences in general stress levels between injured and non-injured students, while repeated-measures ANOVA were performed to investigate whether general stress scores increased before and during injury occurrence. The overall average monthly general stress score over all cohorts for all students was 39.81. The monthly general stress scores ranged from 31.75 to 49.16. Overall, injured and substantially injured students reported higher stress scores than injury-free students, with significant differences in three out of the nine months for all injuries (September, October, March, p = 0.05), and in five months for substantial injuries (September, October, November, December, April, p = 0.05). Within the three-month period before and during injury occurrence, a (marginally) significant linear effect of general stress across the time periods was found for all injuries (F(1.87, 216.49) = 3.10, p = 0.051) and substantial injuries (F(2, 138) = 4.16, p = 0.018). The results indicate an association between general stress and injuries. Future research should focus on effects of varying stress levels on injury risk using higher sampling frequency, for instance by measuring weekly since stress levels are likely to fluctuate daily. Practically, strategies aiming at stress reduction might have the potential to reduce the burden of dance injuries and may have positive outcomes for dancers, teachers, schools and companies.